Analysis of the Influence of SBS Content and Structure on the Performance of SBS/CR Composite Modified Asphalt - Yafeng Gong; Yunze Pang; Fayang Li; Weidong Jin; Haipeng Bi; Yulin Ma (Advances in Materials Science and Engineering)
The performance of asphalt can be improved by adding styrene-butadiene-styrene (SBS) copolymer and crumb rubber (CR). This paper investigated the influence of the structure and content of styrene-butadiene-styrene (SBS) copolymer on the properties of SBS/CR modified asphalt (SBS/CRMA). These SBS/CRMA were prepared by mixing 90# matrix asphalt, 60 mesh CR powder, and SBS copolymers with two molecular structures, which were tested for penetration, softening point, ductility, and rheology. The complex modulus, phase angle, rutting factor, storage modulus, and dissipation modulus of SBS/CRMA were analyzed with the 64°C frequency sweep tests. The results revealed that the content and structure had significant impacts on the performances of SBS/CRMA, and the advantages of SBS polymer network structure in the modified asphalt system cannot be reflected when the amount of SBS was small. Meanwhile, the high-temperature stability, low-temperature tensile resistance, temperature sensitivity, and viscoelasticity of rubberized asphalt were further improved by adding a moderate amount of SBS copolymer. Furthermore, the properties of SBS/CRMA were better as the contents of SBS increased when the type of SBS doped was the same. The effect of modification improved by star-shaped SBS copolymer addition was more than that improved by linear SBS copolymer addition. As a conclusion, the content of 4 wt% star-shaped SBS and 20 wt% CR powder-modified 90# matrix asphalt has the best modification effect with the comparison of other groups.